A preparation method and product of a composite ceramic filter

By using BaZrO3 and Y2O3 raw materials to prepare a multi-phase ceramic filter with multiple pore structures, the shortcomings of existing ceramic filters in high-temperature performance and purification effects are solved, and efficient removal of micron-scale inclusions in titanium alloy melt and automatic capture of Al2O3 non-metal inclusions are achieved.

CN117923944BActive Publication Date: 2025-05-02SHANGHAI JINTUO METAL PROD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410018802.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-05
Publication Date
2025-05-02
Estimated Expiration
2044-01-05

AI Technical Summary

Technical Problem

Existing ceramic filters are difficult to take into account excellent high-temperature performance and good purification effects, especially in removing micron-scale inclusions in titanium alloy melts.

Method used

A multi-phase ceramic filter with multiple pore structures was prepared by in-situ synthesis method using BaZrO3 and Y2O3 as raw materials, and combined with polyurethane foam as carbon source, and obtained by in-situ decomposition carbon source method at high temperature sintering.

Benefits of technology

The prepared composite ceramic filter has high chemical stability and can effectively resist the erosion of highly active melts, especially in removing small-sized inclusions of microns, and can automatically capture and adsorb Al2O3 non-metallic inclusions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004651842320000061
    Figure BDA0004651842320000061
  • Figure BDA0004651842320000071
    Figure BDA0004651842320000071
  • Figure HDA0004651842350000011
    Figure HDA0004651842350000011
Patent Text Reader

Abstract

The invention discloses a preparation method of a composite ceramic filter, comprising the following steps: using BaZrO3 and Y2O3 as raw materials, wherein the ratio of BaZrO3 to Y2O3 is 75-25wt%: 5-75wt%; adding 0.2-1wt% of a dispersant and 15-30wt% of deionized water according to the mass fraction of the mixed raw materials to form a slurry, using a polyurethane foam with a pore size of 30-60PPI as a matrix, applying the slurry on the matrix, and sintering at high temperature by an in-situ decomposition carbon source method after drying. The composite ceramic filter prepared by the present invention can resist the erosion of a high oxidation active alloy melt in terms of use effect, has a good filtering effect for small-sized, especially micron-sized, inclusions, and can also automatically capture and adsorb Al2O3 non-metallic inclusions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of inclusion filters in the metallurgical field, and in particular to a preparation method and product of a composite ceramic filter. Background Art

[0002] Inclusions are one of the important factors affecting alloy quality. Removing inclusions is an important way to improve alloys and steels. Titanium alloys, in particular, have been widely used in aerospace, chemical, and medical fields because of their high specific strength, corrosion resistance, good biocompatibility, good mechanical properties, and processing properties. However, due to the influence of inclusions, its application and development are greatly limited. Inclusions formed during the titanium alloy smelting process will seriously reduce the alloy properties and thus limit the application of titanium alloys in the field of high-end technology. Therefore, it is urgent to reduce the inclusion content in titanium alloys to improve the quality of titanium alloy products.

[0003] In recent years, foam ceramics are a filter medium that can efficiently remove inclusions from molten alloys. In order to effectively improve the quality of alloy products, the filter performance must meet the following requirements: high high-temperature mechanical strength, able to withstand the mechanical impact of high-temperature alloy liquids; good thermal shock resistance, to resist the thermal shock of high-temperature alloy liquids; maintain high chemical stability to alloy liquids at high temperatures, and do not react with alloy elements.

[0004] However, titanium alloy filtration has not been reported yet. Common filters such as "A magnesium oxide foam ceramic filter and its preparation method" (CN200910220791.8) use pure MgO as raw material to prepare the foam ceramic filter, which has a certain adsorption effect on impurities, but MgO is easy to react with high oxidation activity titanium melt. Another example is "A magnesium aluminum spinel foam filter and its preparation method" (CN201310539992.0), which uses spinel or aluminum oxide and magnesium hydroxide as raw materials, and prepares a magnesium aluminum spinel foam filter after high-temperature sintering. The strength is greatly improved, but at high temperature, Al2O3 and MgO in magnesium aluminum spinel will be dissolved by titanium alloy melt to generate [Al] and [Mg], thereby polluting the alloy. Another example is "Porous magnesium oxide-based ceramic filter with multiple pore structures and preparation method thereof" (CN201911398532.4), which uses magnesia as raw material and a two-step method to prepare a magnesium oxide-based ceramic filter with multiple pore structures. It achieves certain results in adsorbing inclusions, but the preparation process is cumbersome, the raw material cost is high, and it is not suitable for large-scale application.

[0005] In short, it is difficult for ceramic filters in the prior art to have both excellent high-temperature performance and good purification effect. Summary of the invention

[0006] In order to overcome the above-mentioned defects of the prior art, the present invention provides a preparation method and product of a composite ceramic filter. It can be applied to the filtration of titanium alloy melt inclusions, and the filter has high chemical stability. It has a better effect on small-sized inclusions, especially micron-sized inclusions, and can automatically capture and adsorb Al2O3 non-metallic inclusions.

[0007] In order to achieve the purpose of the present invention, the technical solution adopted is as follows:

[0008] A method for preparing a composite ceramic filter comprises the following steps:

[0009] BaZrO3 and Y2O3 are used as raw materials, wherein the ratio of BaZrO3 to Y2O3 is 75-25wt%:5-75wt%;

[0010] 0.2-1wt% of dispersant and 15-30wt% of deionized water are added according to the mass fraction of the mixed raw materials to prepare slurry, and polyurethane foam with a pore size of 30-60PPI is used as a matrix. The slurry is dip-coated on the matrix, and after drying, the in-situ carbon source decomposition method is used to obtain the slurry, and high-temperature sintering is performed.

[0011] A method for preparing a composite ceramic filter, the specific steps are as follows:

[0012] (1) BaZrO3 and Y2O3 are weighed in proportion and mixed into powder to obtain a mixed raw material, wherein the ratio of BaZrO3 to Y2O3 is 75-25wt%:5-75wt%;

[0013] Adding 0.2-1 wt% of a dispersant and 15-30 wt% of deionized water to the mixed raw materials, and stirring to form a homogeneous slurry;

[0014] (2) selecting a polyurethane foam with a pore size of 30-60 PPI, soaking the polyurethane foam in an alkaline solution for 1-3 hours, taking it out, washing it with deionized water for several times and then drying it to obtain a pretreated polyurethane foam;

[0015] (3) immersing the pretreated polyurethane foam in the homogenous slurry, and after the pretreated polyurethane foam is evenly adhered to the homogenous slurry, taking it out and placing it in an oven at 110° C. to 130° C. for heating and drying to obtain a green blank,

[0016] The green blank is placed in a high temperature furnace and kept at a temperature of 1500-1700° C. for 4-6 hours and then cooled to obtain a composite ceramic filter product.

[0017] In a preferred embodiment of the present invention, the alkaline solution is a NaOH solution with a pH of 7.0-9.0.

[0018] In a preferred embodiment of the present invention, the high temperature furnace is heated to 800-1000°C at a heating rate of 5-15°C / min and kept warm for 1-3h, so that the carbon source can be fully decomposed and volatilized while Y2O3 can be fully dissolved into ZrO2 in the BaZrO3 raw material to prevent ZrO2 from undergoing phase change and volume change at high temperature and thus causing cracks in the ceramic filter; then the temperature is continued to be raised to 1500-1700°C at a heating rate of 3-10°C / min, kept warm for 4-6h, and taken out after cooling.

[0019] In a preferred embodiment of the present invention, the composite ceramic filter product is specifically a BaZrO3 and Y2O3 composite ceramic filter, the porosity of the composite ceramic filter is 75% to 85%, and the average pore size of the filter is 8-15 μm.

[0020] The beneficial effects of the present invention are:

[0021] The invention directly synthesizes a BaZrO3 and Y2O3 composite ceramic filter with multiple pore structures by an in-situ synthesis method.

[0022] In terms of usage effect, it can resist the erosion of highly active melts, has better effects on small-sized inclusions, especially micron-sized inclusions, and can also automatically capture and adsorb Al2O3 non-metallic inclusions. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 Schematic diagram of the number of inclusions in the product prepared in Example 2 of the present invention, wherein (a) represents the unfiltered alloy; and (b) represents the filtered alloy. DETAILED DESCRIPTION

[0024] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below through the accompanying drawings and embodiments. However, it should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the scope of the present invention. In addition, in the following structure, the description of the known structure and technology is omitted to avoid unnecessary confusion of the concept of the present invention.

[0025] The following is further described by specific embodiments:

[0026] Example 1

[0027] Step 1, weighing raw materials: weighing 50wt% BaZrO3 and 50wt% Y2O3 powders, and mixing the powders in a planetary ball mill for 4h;

[0028] Step 2, slurry preparation: on the basis of the mixed powder, 0.5wt% dispersant and 20wt% deionized water are added, and a homogeneous slurry is prepared by mechanical stirring for 2h;

[0029] Step 3, pretreatment of polyurethane foam: cut the polyurethane foam with a pore size of 30-60 PPI and a porosity of 65-85% into appropriate sizes and soak it in a NaOH solution with a pH of 7.5-8.8 for 2 hours, take it out, wash it with deionized water 6 times and dry it naturally to obtain pretreated polyurethane foam;

[0030] Step 4, blank preparation: immersing the pretreated polyurethane foam in the slurry, taking out and drying naturally after the pretreated polyurethane foam is evenly adhered to the slurry, and then heating and drying in an oven at 150° C. for 12 hours to obtain a ceramic filter blank;

[0031] Step 5, sintering: placing the ceramic filter blank in a high temperature furnace and heating it to 1000°C at a heating rate of 15°C / min, keeping it at that temperature for 3 hours, then heating it to 1700°C at a heating rate of 10°C / min, keeping it at that temperature for 4 hours, and taking it out after cooling. The BaZrO3 and Y2O3 composite ceramic filter product 1 is obtained.

[0032] Example 2

[0033] Step 1, weighing raw materials: weighing 75wt% BaZrO3 and 25wt% Y2O3 powders, and mixing the powders in a planetary ball mill for 4h;

[0034] Step 2, slurry preparation: on the basis of the mixed powder, 0.5wt% dispersant and 30wt% deionized water are added, and a homogeneous slurry is prepared by mechanical stirring for 2h;

[0035] Step 3, pretreatment of polyurethane foam: cut the polyurethane foam with a pore size of 30-60 PPI and a porosity of 65-85% into appropriate sizes and soak it in a NaOH solution with a pH of 7.5-8.8 for 2 hours, take it out, wash it with deionized water 6 times and dry it naturally to obtain pretreated polyurethane foam;

[0036] Step 4, blank preparation: immersing the pretreated polyurethane foam in the slurry, taking out and drying naturally after the pretreated polyurethane foam is evenly adhered to the slurry, and then heating and drying in an oven at 150° C. for 12 hours to obtain a ceramic filter blank;

[0037] Step 5, sintering: Place the ceramic filter blank in a high temperature furnace and heat it to 900°C at a heating rate of 10°C / min, keep it at that temperature for 2 hours, then continue to heat it to 1700°C at a heating rate of 15°C / min, keep it at that temperature for 6 hours, and take it out after cooling. A BaZrO3 / Y2O3 composite ceramic filter 2 of BaZrO3 and Y2O3 is obtained.

[0038] Example 3

[0039] Step 1, weighing raw materials: weighing 75wt% BaZrO3 and 25wt% Y2O3 powders, and mixing the powders in a planetary ball mill for 4h;

[0040] Step 2, slurry preparation: on the basis of the mixed powder, 0.5wt% dispersant and 15wt% deionized water are added, and a homogeneous slurry is prepared by mechanical stirring for 2h;

[0041] Step 3, pretreatment of polyurethane foam: cut the polyurethane foam with a pore size of 30-60 PPI and a porosity of 65-85% into appropriate sizes and soak it in a NaOH solution with a pH of 7.5-8.8 for 2 hours, take it out, wash it with deionized water 6 times and dry it naturally to obtain pretreated polyurethane foam;

[0042] Step 4, blank preparation: immersing the pretreated polyurethane foam in the slurry, taking out and drying naturally after the pretreated polyurethane foam is evenly adhered to the slurry, and then heating and drying in an oven at 150° C. for 12 hours to obtain a ceramic filter blank;

[0043] Step 5, sintering: the ceramic filter blank is placed in a high temperature furnace and heated to 800°C at a heating rate of 8°C / min, kept at that temperature for 2 hours, then continued to be heated to 1650°C at a heating rate of 5°C / min, kept at that temperature for 5 hours, and then taken out after cooling. The BaZrO3 and Y2O3 composite ceramic filter 3 is obtained.

[0044] Example 4

[0045] Step 1, weighing raw materials: weighing 50wt% BaZrO3 and 50wt% Y2O3 powders, and mixing the powders in a planetary ball mill for 4h;

[0046] Step 2, slurry preparation: on the basis of the mixed powder, 0.5wt% dispersant and 25wt% deionized water are added, and a homogeneous slurry is prepared by mechanical stirring for 2h;

[0047] Step 3, pretreatment of polyurethane foam: cut the polyurethane foam with a pore size of 30-60 PPI and a porosity of 65-85% into appropriate sizes and soak it in a NaOH solution with a pH of 7.5-8.8 for 2 hours, take it out, wash it with deionized water 6 times and dry it naturally to obtain pretreated polyurethane foam;

[0048] Step 4, blank preparation: immersing the pretreated polyurethane foam in the slurry, taking out and drying naturally after the pretreated polyurethane foam is evenly adhered to the slurry, and then heating and drying in an oven at 150° C. for 12 hours to obtain a ceramic filter blank;

[0049] Step 5, sintering: placing the ceramic filter blank in a high temperature furnace and heating it to 1000°C at a heating rate of 5°C / min, keeping it at that temperature for 1 hour, then heating it to 1650°C at a heating rate of 3°C / min, keeping it at that temperature for 6 hours, and taking it out after cooling. The composite ceramic filter product 4 of BaZrO3 and Y2O3 is obtained.

[0050] Example 5

[0051] Step 1, weighing raw materials: weighing 75wt% BaZrO3 and 25wt% Y2O3 powders, and mixing the powders in a planetary ball mill for 4h;

[0052] Step 2, slurry preparation: on the basis of the mixed powder, 0.5wt% dispersant and 18wt% deionized water were added, and a homogeneous slurry was prepared by mechanical stirring for 2h;

[0053] Step 3, pretreatment of polyurethane foam: cut the polyurethane foam with a pore size of 30-60 PPI and a porosity of 65-85% into appropriate sizes and soak it in a NaOH solution with a pH of 7.5-8.8 for 2 hours, take it out, wash it with deionized water 6 times and dry it naturally to obtain pretreated polyurethane foam;

[0054] Step 4, blank preparation: immersing the pretreated polyurethane foam in the slurry, taking out and drying naturally after the pretreated polyurethane foam is evenly adhered to the slurry, and then heating and drying in an oven at 150° C. for 12 hours to obtain a ceramic filter blank;

[0055] Step 5, sintering: the ceramic filter blank is placed in a high temperature furnace and heated to 850°C at a heating rate of 12°C / min, kept at that temperature for 1.5 hours, then heated to 1500°C at a heating rate of 8°C / min, kept at that temperature for 5 hours, and taken out after cooling. The BaZrO3 and Y2O3 composite ceramic filter 5 is obtained.

[0056] Table 1 is a comparison table of important steps in each embodiment

[0057]

[0058] Table 2 is a performance test table of each embodiment

[0059]

[0060] Compared with the prior art, the present invention has the following positive effects:

[0061] The present invention utilizes polyurethane organic foam as a carbon source and directly synthesizes a BaZrO3 and Y2O3 composite ceramic filter with a multiple-pore structure through an in-situ decomposition carbon source method. Compared with the preparation process of a traditional foam ceramic filter, the process is simpler and the cost is lower than that of a foaming method and other pore-making methods; and the prepared BaZrO3 / Y2O3 composite ceramic filter has a uniformly distributed pore structure and fewer defects.

[0062] The BaZrO3 and Y2O3 composite ceramic filter with multiple pore structures prepared by the present invention has a more excellent purification ability for filtering high-temperature and high-activity alloy liquids, and has a stronger adsorption ability for micron-sized non-metallic inclusions.

[0063] The product skeleton of the multi-porous BaZrO3 and Y2O3 composite ceramic filter prepared by the present invention has a micro-nano porous structure, has a stronger adsorption capacity for inclusions, and has high filtration efficiency. The multi-porous BaZrO3 and Y2O3 composite ceramic filter prepared by the present invention can automatically capture and adsorb Al2O3 non-metallic inclusions.

[0064] See Figure 1 ,Depend on Figure 1 It can be clearly seen that after the alloy melt is filtered through the composite ceramic filter, the number of inclusions is significantly reduced. After filtration, almost all large-sized inclusions in the alloy matrix are filtered out, leaving only some very small-sized inclusions.

[0065] Existing filters are difficult to resist the erosion of titanium and zirconium alloy melts. Not only do they have a short service life, but they are also prone to generate new inclusions.

[0066] In contrast, the BaZrO3 / Y2O3 composite ceramic filter with multiple pore structures prepared in this embodiment can resist the erosion of highly oxidatively active melts, can automatically capture and adsorb Al2O3 non-metallic inclusions, and has high high-temperature mechanical strength, and is suitable for the purification of titanium and zirconium alloys.

[0067] The basic principles and main features of the invention and the advantages of the invention are shown and described above.

[0068] Those skilled in the art should understand that the present invention is not limited to the above-mentioned embodiments. The above-mentioned embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which shall fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for preparing a composite ceramic filter, characterized in that: The steps are as follows: (1) BaZrO3 and Y2O3 are weighed in proportion and mixed into powders to obtain a mixed raw material, wherein the ratio of BaZrO3 to Y2O3 is 75-25wt%:25-75wt%; Adding 0.2-1 wt% of a dispersant and 15-30 wt% of deionized water to the mixed raw materials, stirring to form a homogeneous slurry; (2) Selecting a polyurethane foam with a pore size of 30-60 PPI, soaking the polyurethane foam in a NaOH solution with a pH of 7.0-9.0 for 1-3 hours, taking it out, washing it with deionized water for several times and then drying it to obtain a pretreated polyurethane foam; (3) immersing the pretreated polyurethane foam into the homogeneous slurry, and after the pretreated polyurethane foam is evenly adhered to the homogeneous slurry, taking it out and placing it in an oven at 110° C. to 130° C. for heating and drying to obtain a green blank, The blank is placed in a high temperature furnace at 1500-1700°C for 4-6 hours and then cooled to obtain a composite ceramic filter product. The composite ceramic filter product is specifically a BaZrO3 and Y2O3 composite ceramic filter. The porosity of the composite ceramic filter is 75%-85%, and the average pore size of the filter is 8-15μm.

2. The method for preparing a composite ceramic filter according to claim 1, characterized in that: The high temperature furnace is heated to 800-1000°C at a heating rate of 5-15°C / min, kept at that temperature for 1-3 hours, and then continued to be heated to 1500-1700°C at a heating rate of 3-10°C / min, kept at that temperature for 4-6 hours, and then taken out after cooling.

Citation Information

Patent Citations

  • Magnesia ceramic foam filter and preparation method thereof

    CN101708401A

  • Magnesium aluminate spinel foamed ceramic filter as well as preparation method thereof

    CN103553686B

  • Porous magnesium oxide-based ceramic filters with multi-pore structure and their preparation method

    CN111099881B

  • Yttria foamed ceramic filter and preparation method thereof

    CN102000458A